Active auroral arc powered by accelerated electrons from very high altitudes - Imajo, Shun; Miyoshi, Yoshizumi; Kazama, Yoichi; Asamura, Kazushi; Shinohara, Iku; Shiokawa, Kazuo; Kasahara, Yoshiya; Kasaba, Yasumasa; Matsuoka, Ayako; Wang, Shiang-Yu; Tam, Sunny W. Y.; Chang, Tzu‑Fang; et al. (Scientific reports, 2021)
Bright, discrete, thin auroral arcs are a typical form of auroras in nightside polar regions. Their light is produced by magnetospheric electrons, accelerated downward to obtain energies of several kilo electron volts by a quasi-static electric field. These electrons collide with and excite thermosphere atoms to higher energy states at altitude of ~ 100 km; relaxation from these states produces the auroral light. The electric potential accelerating the aurora-producing electrons has been reported to lie immediately above the ionosphere, at a few altitudes of thousand kilometres 1 . However, the highest altitude at which the precipitating electron is accelerated by the parallel potential drop is still unclear. Here, we show that active auroral arcs are powered by electrons accelerated at altitudes reaching greater than 30,000 km. We employ high-angular resolution electron observations achieved by the Arase satellite in the magnetosphere and optical observations of the aurora from a ground-based all-sky imager. Our observations of electron properties and dynamics resemble those of electron potential acceleration reported from low-altitude satellites except that the acceleration region is much higher than previously assumed. This shows that the dominant auroral acceleration region can extend far above a few thousand kilometres, well within the magnetospheric plasma proper, suggesting formation of the acceleration region by some unknown magnetospheric mechanisms.